Using of cryoprotectors for low-temperature storage of seed material of Thymus rasitatus - Gavrilkova, E.А.; Dodonova, А.Sh.; Тleukenova, S.U.; Ishmuratova, М.Yu.; Verzhuk, V.G. (KSU publ., 2017)
In article influence of various cryoprotectors on preserving viability of the seed material of Thymus rasitatus is studied and described. As a result of the conducted researches it is established that for Thymus rasitatus seeds the best storage conditions allowing to keep the highest rates of viability is use of a plastic container, a cryoprotector — 5% DMSO and slow defrosting at the room temperature. At the same time increase in level of energy of germination and viability by 15% and 10,7% in comparison with control is observed. After analyzing dynamics of seed germination of the researched species it was established that the seeds which were previously processed by glycerin and 5% DMSO with the subsequent cryopreservation sprout quicker and phases of development pass rather.
Thymus rasitatus тұқымдық материалының төмен температурада сақтау кезінде криопротекторларды қолдану
Использование криопротекторов при низкотемпературном хранении семенного материала Thymus rasitatus
Keywords: Thymus rasitatus; cryoprotector; cryoconservation; DMSO; glycerin; germination; germinative energy; endemics